PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PASAR DAN KINERJA KEUANGAN PERUSAHAAN - Claudia, Andriane; Afri Yuyetta, Etna Nur (Diponegoro Journal of Accounting, 2016)
The aim of this study is to examine the influence of intellectual capital on financial performance and market value of the company. Independent variable used in this study is intellectual capital which measured by VACA, VAHU, and STVA, while dependent variable are financial performance consists of Return on Asset, Return on Equity, Growth Revenue, and Economic Value Added, and the market value measure by Market to Book ValueThe population used in this study consist of stated-own enterprises listed on the Indonesia Stock Exchange in 2010-2014. The sampling method used in this study is purposive sampling and obtained 17 companies. This study uses multiple regression analysis for hypotheses testing.The results of this study showed that intellectual capital simultaneously influence in return on asset, return on equity, growth revenue, economic value added and market to book value, but when its component partially tested, each component showed a different effect to the dependent variables.